A new method for numerical solution of checkerboard fields. Issue 4 (1st January 2002) - Berggren, Stein A.; Lukkassen, Dag; Meidell, Annette; Simula, Leon
Abstract : We consider a generalized version of the standard checkerboard and discuss the difficulties of finding the corresponding field by standard numerical treatment. A new numerical method is presented which converges independently of the local conductivities.